2021
DOI: 10.1007/s11145-021-10205-x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and outcomes of behavioral engagement in the context of text comprehension: when quantity means quality

Abstract: Using a path analytic approach with a sample of Norwegian undergraduate readers, we investigated the effects of behavioral engagement on text comprehension as reflected in students’ post-reading written reports on the topic in question. Results indicated that the behavioral engagement components of writing time and the length of the written responses had distinctive, unique effects on comprehension performance, and that behavioral engagement also mediated the effects of cognitive (prior knowledge, working memo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 48 publications
0
4
0
1
Order By: Relevance
“…Working memory was measured with a Norwegian adaptation of Swanson and Trahan’s (1992) Working Memory Span Task, which is based on the technique originally developed by Daneman and Carpenter (1980) . The Norwegian adaptation has been used and validated in much prior work with postsecondary students (e.g., Delgado et al, 2020 ; Bråten et al, 2022 ; Haverkamp and Bråten, 2022 ). The materials consisted of 42 unrelated declarative sentences, five to 12 words in length, which were organized into 12 sets of sentences.…”
Section: Methodsmentioning
confidence: 99%
“…Working memory was measured with a Norwegian adaptation of Swanson and Trahan’s (1992) Working Memory Span Task, which is based on the technique originally developed by Daneman and Carpenter (1980) . The Norwegian adaptation has been used and validated in much prior work with postsecondary students (e.g., Delgado et al, 2020 ; Bråten et al, 2022 ; Haverkamp and Bråten, 2022 ). The materials consisted of 42 unrelated declarative sentences, five to 12 words in length, which were organized into 12 sets of sentences.…”
Section: Methodsmentioning
confidence: 99%
“…Working Memory Capacity. Working memory capacity was measured with a Norwegian adaptation of Swanson and Trahan's (1992) Working Memory Span Test that has been validated in several previous studies with adult readers (e.g., Bråten et al, 2022;Delgado et al, 2020). Twelve sets of unrelated sentences, varying from two to five sentences in each set, were read aloud to participants.…”
Section: Control Variablesmentioning
confidence: 99%
“…Processing time has been found to predict multiple text comprehension (e.g., Bråten et al, 2014;. A second, validated measure of behavioral engagement is the extent of the written task product used to assess comprehension performance in response to open-ended integrative questions or essay tasks (Bråten et al, 2022;Latini et al 2019). Bråten et al (2022) investigated the effects of two components of behavioral engagement, writing time and response length, on text comprehension.…”
Section: Informational Context Engagement and Integrationmentioning
confidence: 99%
“…A second, validated measure of behavioral engagement is the extent of the written task product used to assess comprehension performance in response to open-ended integrative questions or essay tasks (Bråten et al, 2022;Latini et al 2019). Bråten et al (2022) investigated the effects of two components of behavioral engagement, writing time and response length, on text comprehension. Findings showed that these components had unique and differential effects on comprehension and that behavioral engagement mediated the effects of cognitive and motivational individual differences on comprehension performance.…”
Section: Informational Context Engagement and Integrationmentioning
confidence: 99%